2020
DOI: 10.1002/celc.202000878
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Electrochemical Oxidation on Physicochemical Properties of Fe‐Containing Single‐Walled Carbon Nanotubes

Abstract: Metal catalysts are necessary for fabricating carbon nanotubes, but are often considered impurities in the end products, and arduous steps are used to remove catalyst residues from the nanotube structure. However, as metals can be electrocatalytic, instead of removing them we can utilize their role in detection of analgesics. Herein, we study the physicochemical properties of Fe-containing single-walled carbon nanotubes (SWCNTs), and the effect of simple oxidative pretreatment on them. We show that a gentle an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 42 publications
(84 reference statements)
1
1
0
Order By: Relevance
“…Likewise, AA has been shown to experience a similar cathodic shift in its oxidation potential in the presence of similar oxygen functionalities . Moreover, our recent investigations show that PA also experiences a cathodic shift in its oxidation potential upon oxidative treatment of single-wall carbon nanotube (SWCNT) network electrodes . Because an opposite trend is seen here in all of the previously discussed cases, some species other than oxygen in the system must cause this inhibition of the reaction on the nitrogenated electrode surfaces.…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…Likewise, AA has been shown to experience a similar cathodic shift in its oxidation potential in the presence of similar oxygen functionalities . Moreover, our recent investigations show that PA also experiences a cathodic shift in its oxidation potential upon oxidative treatment of single-wall carbon nanotube (SWCNT) network electrodes . Because an opposite trend is seen here in all of the previously discussed cases, some species other than oxygen in the system must cause this inhibition of the reaction on the nitrogenated electrode surfaces.…”
Section: Resultssupporting
confidence: 58%
“…39 Moreover, our recent investigations show that PA also experiences a cathodic shift in its oxidation potential upon oxidative treatment of singlewall carbon nanotube (SWCNT) network electrodes. 58 Because an opposite trend is seen here in all of the previously discussed cases, some species other than oxygen in the system must cause this inhibition of the reaction on the nitrogenated electrode surfaces. Furthermore, the response of nitrogenated amorphous carbon films toward DA oxidation was recently investigated by Behan et al 23 Their results indicated that there was a slight increase in the oxidation current of DA (but no change in the oxidation potential) on nitrogen-containing film in comparison with nitrogen-free film: The I p value increased linearly as a function of the scan rate, and the peaks were symmetric, pointing toward the weak adsorption of reaction species on the surface of nitrogenated a-C electrodes.…”
Section: ■ Introductionmentioning
confidence: 54%